Design development of a copper-coated canister for the disposal of spent fuel in a deep geological repository in Opalinus Clay. (28th April 2017) - Diomidis, Nikitas; Johnson, Lawrence H.; Bastid, Philippe; Allen, Chris
ABSTRACT: Nagra is currently developing design concepts for canisters for the deep geological disposal of spent fuel and high-level waste. A feasibility evaluation study was done to assess a number of candidate canister designs and materials. The potential canister options were assessed with regard to long-term safety by considering mechanical integrity, environmental damage and potential impact on the geological barrier. Manufacturing feasibility, sealing, inspection as well as potential cost were also assessed. A canister concept, based on a thick-walled forged carbon steel substrate coated with copper, was favourably assessed. As a result, development work was undertaken to refine the copper-coated canister design. Different lid designs and closure configurations were considered, using finite element analysis, to determine the limit load by plastic yielding and buckling and to determine safety margins under the design load. In addition, finite element fracture analyses were performed to determine stress intensity factors at the closure weld root. A hemispherical lid with a partially penetrating weld at a depth of 25–32 mm, having a root gap in the axial direction, was found to be fit for purpose while offering the potential to avoid post-weld heat treatment. An evaluation of relevant welding processes for closure welding of the selected joint design was then carried out. The potential welding processes were ranked based on a number of criteria linked to the maturity of the technique, the quality of the resulting weld, the properties of the weld material, and the applicability of the technique to the current canister design and the requirements of deployment in a hot cell. This paper is part of a supplement on the 6th International Workshop on Long-Term Prediction of Corrosion Damage in Nuclear Waste Systems.